1996
DOI: 10.1007/s004300050025
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a 33-kDa protein antigen from delipidified Mycobacterium tuberculosis H 37 Rv

Abstract: A 33-kDa protein (TB33) was isolated from a delipidated cell sonicate (CS) of Mycobacterium tuberculosis H37Rv (grown in Middlebrook 7H9 broth supplemented with glucose) using immobilized metal affinity chromatography (IMAC) on a nickel-nitrilotriacetic acid (Ni-NTA) column. TB33 could not be isolated from the culture filtrate (CF) of M. tuberculosis H37Rv using Ni-NTA. TB33 was recognized by monoclonal antibodies (mAb) known to react with proteins of M. tuberculosis with a molecular mass of 33/34 kDa; namely,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Nonsecreted or cytoplasmic proteins of mycobacteria have generally not been found to be major antigenic targets of T cell responses in M. tuberculosis-infected animals, although humoral responses have sometimes been found against such antigens (156)(157)(158). However, the fact that nonsecreted mycobacterial proteins do not strongly stimulate T cell responses during infection with live mycobacteria does not necessarily mean that these antigens cannot be the targets for protective T cell responses.…”
Section: Secreted Proteins As Immunological Decoysmentioning
confidence: 99%
“…Nonsecreted or cytoplasmic proteins of mycobacteria have generally not been found to be major antigenic targets of T cell responses in M. tuberculosis-infected animals, although humoral responses have sometimes been found against such antigens (156)(157)(158). However, the fact that nonsecreted mycobacterial proteins do not strongly stimulate T cell responses during infection with live mycobacteria does not necessarily mean that these antigens cannot be the targets for protective T cell responses.…”
Section: Secreted Proteins As Immunological Decoysmentioning
confidence: 99%
“…This has been observed for antigens such as ESAT‐6 and Ag85B, which are secreted early after infection and tend to dominate as targets of the T‐cell responses in experimentally infected animals or humans with naturally acquired tuberculosis. On the other hand, T‐cell responses to cytosolic nonsecreted proteins have generally been found to be absent or weak in infected animals, although cellular and humoral responses have occasionally been reported to these (29–32). Recent experiments comparing M. tuberculosis strains that were engineered to either secrete or retain within the bacterial cell the antigen CFP‐10 confirmed that CD4 + and CD8 + T‐cell responses in vivo to this normally immunodominant antigen are dependent on its secretion (33).…”
Section: Antigenic Targets Of T‐cell Responses To M Tuberculosismentioning
confidence: 99%
“…Nonsecreted or cytoplasmic proteins of mycobacteria have generally not been found to be major antigenic targets of T‐cell responses in M. tuberculosis ‐infected animals, although humoral responses have sometimes been found against such antigens (29, 31, 32). However, the fact that nonsecreted mycobacterial proteins do not strongly stimulate T‐cell responses during infection with live mycobacteria does not necessarily mean that these antigens cannot be the targets for protective T‐cell responses.…”
Section: Strategies For Evasion or Subversion Of T‐cell Responses By mentioning
confidence: 99%